WATER REQUIREMENTS MODELLING IN PRODUCING RED SPINACH (AMARANTHUS TRICOLOR) MIRA VARIETY USING CAPILLARY WICK IRRIGATION AT DIFFERENT LIGHT INTENSITIES AS AN INITIAL DESIGN OF HYPER URBAN FARMING SYSTEM - Intan Sanubari, Muthia
One of the challenges in the development of an urban agricultural system is the existence of competition between plant water needs and human water needs. Modeling of water requirements or evapotranspiration (ETc) is required for efficient water use in urban agricultural systems. This study aims to determine the model of ETc at different light intensities. The method used is the measurement of actual ETc and ETc Penman- Monteith on the capillary wick irrigation system stored in an unshaded (T1) and shaded (T2) place. Red spinach was used as a model plant. Based on the study, it was found that the actual ETc accumulation value of plants under shaded conditions was 1.42 times greater than the Penman-Monteith ETc with quality R2 = 0.99. The accumulated value of the actual ETc of shaded plants was 1.81 times greater than the Penman- Monteith ETc with quality R2 = 0.99. Modelling of the effect of actual water needs on height at T1 and T2 both has R2 = 0.99. Modeling of the effect of water needs on the number of leaves on T1 plants had R2 = 0.98 and T2 plants had R2 = 0.99. The difference in light intensity had a significant effect on high growth, number of leaves, wet weight and dry weight (roots, stems, leaves).